AN ANALYSIS OF ENGLISH VERBS TRIGGERING PRESUPPOSITION IN ROBERT GALBRAITH’S NOVEL THE CUCKOO’S CALLING - Suhardiman, Sani; Sihombing, Boyman; Juraida, Anita (International Journal of Psychosocial Rehabilitation, 2020)
This study entitled An Analysis of English verbs triggering presupposition in Robert Galbraith Novel’s The Cuckoos Calling is aimed at finding out the types of verbs triggering presupposition, verbs triggering presupposition, and frequency of occurrences of types of verbs triggering presupposition. This study belongs to descriptive qualitative method. The research object of this study is utterances containing verbs triggering presupposition. The data were collected from the novel The Cuckoo’s Calling. The researcher used noting technique, separating technique, and transferring technique in collecting the data. In analyzing data, the researcher used padan ekstralingual. The findings show that (1) there are five types of verbs which trigger the presupposition in the novel The Cuckoos Calling namely factive verb, implicative verb, aspectual/change of state verb, verb of judging, and iterative verb; (2) Each types of verbs in the point have different verbs; (3) the percentage of the types of verbs triggering presupposition are, the aspectual/change of state verb has 33.96%, implicative verbs 26.41%, factive verbs 32.07%, verbs of judging 1.78 %, and iterative verbs 5.66%.